The Relationship of Gold Price with the Stock Market: The Case of Frankfurt Stock Exchange - Al-Ameer, Maryam; Hammad, Walaa; Ismail, Areej; Hamdan, Allam (International Journal of Energy Economics and Policy, 2018)
This paper considers the relationship between two main economic variables: Gold & Stock market in Germany that is represented by the HDAX Index under the FSE. The researchers used monthly data collected from Bloomberg database spanning from August 2004 to September 2016 (12 years) in order to use them in the selected tests in this research which are: (Descriptive statistic tests, Pearson’s correlation test, Unit root test to assure data are stationary for the Johansen’s Co-integration test and the Granger Causality test.) The data were divided into three periods: pre, during and post to financial crisis in order to measure the different effect in each period. The results showed that there is a correlation between gold and stock market that differs in each period, as for the whole period of 12 years there was a moderate positive correlation, before the financial crisis there was a very strong positive correlation, during the financial crisis the correlation was positive but weak and low which means its insignificant, while at the period after the financial crisis the correlation changed in nature as it became a strong high negative correlation. The co-integration test results were all the same for all the three different periods (before, during and after financial crisis) and also for the whole 12 years period that is there is a long run relationship between gold and stock market (represented by the HDAX Index). The same thing applies on the Granger causality test, as there was no Granger causality (No Cause-effect relationship) between gold and stock market. Keywords: Gold Price, Stock Market, Frankfurt Stock Exchange (FSE), HDAX Index, JEL Classifications: C01, C58, G01, G11 and G15.